Intermittent afatinib treatment suppresses the growth of resistant T790M-H1975 cells in non-small cell lung cancer (NSCLC) co-culture - Faisal Hamdi, Amir Imran; Poh, Wen Tsin; Lim, Jonathan Chee Woei; Daut, Ummi Nadira; How, Soon Hin; Pang, Yong Kek; Stanslas, Johnson (Walter de Gruyter GmbH, 2025)
Objectives: Most non-small-cell lung cancers (NSCLC) that harbour an epidermal growth factor receptor (EGFR) mutation are treated with afatinib. Resistance emerges in most patients, making treatment ineffective. Reports suggest intermittent treatment (IT) delays the emergence of resistance compared to standard-of-care continuous treatment (CT). Thus, this study aimed to investigate the efficacy of afatinib through both treatments in NSCLC in vitro. Methods: The growth inhibition of afatinib was evaluated in mixed co-culture lines of HCC827 (sensitising with exon 19 deletion) and H1975 (resistant with L858R/T790M), with resistant percentages of 0.1% and 0.5 % treated with afatinib at 100 and 500 pM (pM). CT was treated for 96 h, while IT was treated for 24 h and was treatment-free for 72 h. They were assessed at 192 h with cell counting and qPCR with cell line-specific primers targeting exon 19 deletion and L858R, followed by images of fluorescent resistance. Results: At 96 and 192 h, IT had a higher cell count than CT in both 0.1 % and 0.5 % resistance at 100 and 500 pM (p<0.05). The qPCR analysis showed the gene expression for resistant cells in IT was lower than in CT (p<0.05). However, nanomolar concentrations in patients’ pharmacokinetics resulted in resistance dominance and progression. Conclusions: Overall, in both 0.1% and 0.5 % resistance in co-cultures, intermittent treatment allows a significant portion of viable sensitive cells to suppress the growth of resistant cells at concentrations of both 100 and 500 pM. Collectively, IT delays the emergence of de novo resistance with low resistance at specific concentrations. These findings offer the potential for utilising alternative treatment strategies as opposed to continuous treatment to improve therapeutic outcomes in NSCLC.